Diagnostic value of metagenomic next-generation sequencing combined by medical thoracoscopy surgery among infectious pleural effusion patients - Nannan Gao; Saran Feng; Xiaoxiao Yu; Jing Zhao; Yunyan Wan; Zhouhong Yao; Dezhi Li (BMC Infectious Diseases)
Abstract Background Metagenomic next-generation sequencing (mNGS) is a novel method for identifying pathogens in infectious diseases. This study aimed to explored the application value of mNGS in diagnosing pulmonary infections with pleural effusion, confirmed by medical thoracoscopy. Methods We retrospectively reviewed 25 patients with pulmonary infections and pleural effusion between July 2020 and December 2021. All patients had their diagnosis confirmed by medical thoracoscopy to obtain tissue samples for both traditional testing and mNGS. Samples included pleural effusion, successive sputum, and tissue obtained through medical thoracoscopy. We wanted to assess how effective mNGS was in accurately diagnosing these infections. Results This study found that the positive predictive value of mNGS (76% (19/25)) was significantly higher than that of traditional testing (32% (8/25)). The most commonly identified pathogens were Mycobacterium tuberculosis (n = 5), followed by Fusobacterium nucleatum (n = 4), Torque teno virus (n = 4), Streptococcus intermedius (n = 3), Peptostreptococcus stomatis (n = 2), Porphyromonas endodontalis (n = 2), and Campylobacter rectus (n = 2). The percentage of mNGS-positive cases was significantly higher than that from traditional testing for bacteria, but the superiority of mNGS for tuberculosis detection was insignificant. Ten cases were identified with mixed infections by mNGS, while no mixed infections were found by traditional testing. Conclusions Our study showed that using mNGS in combination with biopsy samples obtained through medical thoracoscopy resulted in higher positive rates compared to traditional tests and provided more evidence of pathogens for patients with infectious pleural effusion.